2019
DOI: 10.1002/ecs2.2845
|View full text |Cite
|
Sign up to set email alerts
|

Management regime and habitat response influence abundance of regal fritillary (Speyeria idalia) in tallgrass prairie

Abstract: The >2,570,000-ha Flint Hills ecoregion of Kansas, USA, harbors the largest remaining contiguous tract of tallgrass prairie in North America, a unique system, as the remainder of North America's tallgrass prairie has succumbed to development and conversion. Consequently, the loss and degradation of tallgrass prairie has reduced populations of many North American prairie-obligate species including the regal fritillary (Speyeria idalia) butterfly. Population abundance and occupied range of regal fritillary have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(154 reference statements)
1
4
0
Order By: Relevance
“…Generally speaking, our model findings are consistent with other studies investigating land cover as an indicator of butterfly habitat quality, and thus abundance (Early et al, 2008;Perovi c et al, 2015;Pogue et al, 2016;Post van der Burg et al, 2020;Slancarova et al, 2014). Specifically, the effects of both grassland and forest cover appear consistent with other studies of regal occurrence and indicate that regals prefer to use locations surrounded by grassland with little to no tree cover (Caven et al, 2017;McCullough et al, 2019;Powell et al, 2007;Ries & Debinski, 2001;Selby, 2007). However, this was not a consistent pattern in the sense that our maps of abundance follow the distribution of grasslands.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Generally speaking, our model findings are consistent with other studies investigating land cover as an indicator of butterfly habitat quality, and thus abundance (Early et al, 2008;Perovi c et al, 2015;Pogue et al, 2016;Post van der Burg et al, 2020;Slancarova et al, 2014). Specifically, the effects of both grassland and forest cover appear consistent with other studies of regal occurrence and indicate that regals prefer to use locations surrounded by grassland with little to no tree cover (Caven et al, 2017;McCullough et al, 2019;Powell et al, 2007;Ries & Debinski, 2001;Selby, 2007). However, this was not a consistent pattern in the sense that our maps of abundance follow the distribution of grasslands.…”
Section: Discussionsupporting
confidence: 90%
“…Around each grassland pixel, we computed the amount of grassland and forest found within 1 km. Others have pointed out that abundances of this species are likely higher in areas with larger expanses of intact grassland and lower amounts of forest cover (McCullough et al, 2019). We also computed the distance of each grassland pixel to the nearest human‐developed area, which served as an index of how easy a pixel was to access by surveyors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis et al (2007) reported the majority of species they recorded in tallgrass prairie responded positively to litter. McCullough et al (2019) reported densities of the prairie specialist Speyeria idalia increased with litter cover. Callophrys irus , a rare fire‐dependent butterfly in the Eastern United States, pupates in litter above the soil 92% of the time (Selfridge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We burned three‐fourth of each pasture by the end of this study, but a full application of patch‐burn grazing would mean that each unit in the pastures have received fire at least once (Allred, Fuhlendorf, Engle, et al, 2011 ; Archibald et al, 2005 ; Fuhlendorf & Engle, 2004 ). More years of fire application would also result in greater sample size for each time since fire benchmark (recently burned, 1, 2, 3 years since fire) and more statistical power to determine how time since fire affects specific species and the pollinator community (McCullough et al, 2019 ; Moranz et al, 2012 , 2014 ; Potts et al, 2003 ). Overall butterfly abundance and richness were higher in cattle pastures, but our community analysis did not find a strong association between grazer treatment or site characteristics and patterns of variation in the butterfly community.…”
Section: Discussionmentioning
confidence: 99%